Dynamic Fracture Toughness and Dynamic Tensile Strength of the Rock from Different Depths of Beijing Datai Well. (29th August 2018) - Man, Ke; Liu, Xiaoli
Abstract : From the standard test method suggested by ISRM and GB/T50266-2013, the uniaxial static tensile strength, dynamic tensile strength, and dynamic fracture toughness of the same basalt at different depths have been measured, respectively. It is observed that there may be an empirical relation between dynamic fracture toughness and dynamic tensile strength. The testing data show that both the dynamic fracture toughness and dynamic tensile strength increase with the loading rate and the dynamic tensile strength increases a little bit more quickly than the dynamic fracture toughness. With an increasing depth, the dynamic tensile strength has much more influence on the dynamic fracture toughness, as which it is much liable to bring out the unexpected catastrophes in the engineering projects, especially during the excavation at deep mining. From the rock failure mechanisms, it is pointed out that the essential reason of the rock failure is the microcrack unstable propagation. The crack processes growth, propagation, and coalescence are induced by tensile stress, not shear stress or compressive stress. The paper provides estimation of the dynamic fracture toughness from the dynamic tensile strength value, which can be measured more easily.